(untitled) (Research, Society and Development, 2020)
Most fairs have inadequate hygienic aspects regarding the sale of food, so that marketers acting as food handlers, can become vectors of pathogens for food and consequently for the population. Therefore, taking into account the lack of structure of the Feira Livre de Barreirinhas and the lack of information from the handlers regarding personal hygiene, it remains to analyze what types of parasites present in the hands and nails of the food handlers of the place in question, through conducting parasitological collections in order to analyze them in a Specific Laboratory. In this sense, this study aimed to analyze the types of parasitological beings found in the body members alluded to by the entrepreneurs of Feira Livre in the city mentioned above and to sensitize them regarding health care. The results showed the presence of pathological microorganisms in the bodies of the entrepreneurs, which are a danger to the health of the citizens of Barreirinhas. For this reason, the Municipal Government was instructed to carry out Health Education activities and inspections to comply with the health laws in force in the Brazilian Nation.